2009
DOI: 10.1080/09593330902990089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the use of fly ash as a binder on the mechanical behaviour of treated dredged sediments

Abstract: The objective of this work was to evaluate the suitability of dredged sediments treated with pozzolanic binders as a pavement base material, and to assess the usefulness of fly ash as a soil mixture/binder with the aim of improving the engineering properties of the stabilized dredged sediments in order to make them capable of taking more load from the foundation structures. Comparing the results with other binders currently used in road construction, the addition of fly ash shows significant positive advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
0
9
0
6
Order By: Relevance
“…Dans les propositions de formulations, il a été retenu la chaux comme pouvant agir sur la matière organique (REY, 1999) et la substitution du ciment par un liant pouzzolanique (SILITONGA et al, 2008(SILITONGA et al, , 2009(SILITONGA et al, , 2010 …”
Section: Choix Et Validation D'une Formulationunclassified
“…Dans les propositions de formulations, il a été retenu la chaux comme pouvant agir sur la matière organique (REY, 1999) et la substitution du ciment par un liant pouzzolanique (SILITONGA et al, 2008(SILITONGA et al, , 2009(SILITONGA et al, , 2010 …”
Section: Choix Et Validation D'une Formulationunclassified
“…De plus ces additifs jouent un rôle sur la teneur en eau, la teneur en matières organiques, sur la résistance à long terme. L'effet pouzzolanique n'est pas considéré ici car des essais au-delà de 28 jours sont nécessaires (LEVACHER et al, 2008 ;SILITONGA et al, 2009 …”
Section: Approche éConomique Et Validation De Méthodes De Traitementsunclassified
“…At this case we consider that, the chemical properties of Silica Fume used in this study, are not high enough to make any different. According to regulation [4], after the addition of silica fume and hydraulic binders, the UCS values should reach at least 1 MPa at 28 days of curing age. The test confirmed that all samples after stabilization process could be reused as a material in road construction.…”
Section: Unconfined Compressive Strength (Ucs)mentioning
confidence: 99%
“…[3]. Silitonga E., [4] needed 11% of pozzolanic binders (fly ash) to stabilized dredged sediment from Port de Cherbourg (France). Zhibo in his research, stabilized marine dredged sediment from Port of Cherbourg (France) with 15% hydraulics binder.…”
Section: Introductionmentioning
confidence: 99%